2014
DOI: 10.1111/exd.12572
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis is not an autoimmune disease?

Abstract: The concept that psoriasis is an autoimmune disease needs to be questioned. The autoimmune label has been based on molecular mimicry between streptococcal and keratin proteins and the existence of homologous peptides between these proteins. However, it is only peripheral blood CD8, and not CD4, T lymphocytes that respond to the homologous peptides. This ignores the fact that it is CD4 T cells which are necessary to initiate psoriasis. Recent studies on skin bacterial microbiota have found a variety of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 63 publications
1
38
0
2
Order By: Relevance
“…It has been known for a long time that patients with CD and their first-degree relatives have increased risk of developing psoriasis and vice versa (Egeberg et al 2016). Very recently, it was proposed that similar to CD (Øyri et al 2015), psoriasis could be a result of breakdown of immune tolerance (dysbiosis) to cutaneous bacteria (Fry et al 2013, 2015). According to the aforementioned theory, genetic abnormalities affecting especially innate immune response facilitate initiation of inflammatory response to cutaneous microbiota (Skroza et al 2013; Terziroli Beretta-Piccoli et al 2017; Vlachos et al 2016; Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a long time that patients with CD and their first-degree relatives have increased risk of developing psoriasis and vice versa (Egeberg et al 2016). Very recently, it was proposed that similar to CD (Øyri et al 2015), psoriasis could be a result of breakdown of immune tolerance (dysbiosis) to cutaneous bacteria (Fry et al 2013, 2015). According to the aforementioned theory, genetic abnormalities affecting especially innate immune response facilitate initiation of inflammatory response to cutaneous microbiota (Skroza et al 2013; Terziroli Beretta-Piccoli et al 2017; Vlachos et al 2016; Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…), and in turn, these AMPs could contribute to the induction of PLE. Similarly, damage to commensals may give rise to commensal‐associated molecular patterns (CAMPS) (S18, S19), resulting in microbial signals, altering the skin's microbial landscape and contributing to abnormal immune responses in inflammatory diseases such as psoriasis and beyond. In this regard, studies indicate that photoprovoked PLE patients show an upregulation of certain AMPs (S20).…”
Section: Hypothesis and Premisesmentioning
confidence: 99%
“…13 Five types of psoriasis have been described with chronic plaque psoriasis (psoriasis vulgaris) by far the most common form responsible for approximately 90% of cases. 13 Most of the genetic loci predisposing an individual to psoriasis have been identified by genome-wide linkage analysis and are involved with both acquired and innate immunity, 13, 14 and it has been demonstrated that an aberrant immune response to antimicrobial peptide LL-37 is likely involved in psoriasis immunopathogenesis. 15 It is becoming increasingly evident that psoriasis has a microbial component and that infections may cause disease exacerbation.…”
Section: Introductionmentioning
confidence: 99%